Environmentally benign general synthesis of nonconsecutive carbon-coated RuP2 porous microsheets as efficient bifunctional electrocatalysts under neutral conditions for energy-saving H2 production in hybrid water electrolysis. Issue 13 (31st May 2022) - Li, Yapeng; Wang, Wentao; Cheng, Mingyu; Qian, Qizhu; Zhu, Yin; Zhang, Genqiang
Abstract : A nonconsecutive carbon-coated RuP2 porous microsheet (RuP2 @InC-MS) with bifunctionality for HzOR and HER is realized. DFT calculations evidence that C is more thermoneutral for HER while Ru boosts the dehydrogenation kinetics during HzOR process. Abstract : Electrocatalytic H2 generation under mild neutral conditions is an attractive proposition yet underdeveloped. Herein, a series of nonconsecutive carbon-coated RuP2 porous microsheets (RuP2 @InC-MSs) was synthesized through an environmentally benign one-pot thermolysis route using low-cost and safe P-containing small molecules as phosphorization agents, including guanidine phosphate, amidinourea phosphate, and ammonium phosphate. Benefitting from the unique dual active site exposure, the RuP2 @InC-MSs acted as superior bifunctional electrocatalysts in neutral electrolyte towards both the hydrazine oxidation reaction (HzOR, −48 mV@10 mA cm −2 ) and hydrogen evolution reaction (HER, −83 mv@10 mA cm −2 ), thus demonstrating the energy-saving H2 production in a two-electrode hybrid water electrolyzer (0.366 V@10 mA cm −2 ). Further, an integrated solar-to-H2 device generated abundant green H2 gas with a current of 146 mA under natural sunlight, demonstrating its great potential for coupling applications with sustainable energy resources. This work provides guidelines for constructing metal phosphide–carbon nanohybrids, and facilitates the development of energy-efficient neutral H2 production.